(untitled) (Superficies y Vacío, 2018)
Degradation of paper through time can be measured by monitoring the intensity changes in the band located at 620 nm of its emission fluorescence spectra. The behavior of this band is closely related to the structural stability of the short cellulose chains. A fast degradation of these cellulose chains, mainly lignin, translates in the rapid denaturation of paper occurring at its first aging state. This work proposes a method to reincorporate short cellulose chains in the structure of aged paper through its immersion during 24 h in a solution based on ethyl alcohol and extracts of wood pieces. Results of fluorescence spectra measurements indicate that the short cellulose chains in the solution get embedded in the old paper, making the shape and intensity of the fluorescence emission spectra peaks of new and old paper almost indistinguishable. This behavior provides a desirable approach to analyze, preserve and restore aged paper documents.